Exploring two measures of spatial accessibility to organizational resources in a small city. Issue 3 (27th May 2019) - Meier, Cristian L.; Gilster, Megan E.
ABSTRACT: Research has documented neighborhood-level disparities in organizational resources. Organizational resources may meet residents' needs because, as social organization theory suggests, they generate social ties, establish and enforce local norms, and promote social control. However, few studies have examined access to organizational resources in micropolitan cities, which are important for research on place and inequality because of their growing population and poverty. This study presents findings from an assessment conducted in a Midwestern micropolitan city implementing a new community development initiative. We collected data on program delivery locations and assessed spatial accessibility using two measures of organizational resources in neighborhoods: (1) the count of programs and (2) the average distance to all programs from a neighborhood centroid. Findings reveal distinct characteristics of micropolitan geography. Access to resources was not equitably distributed. However, neighborhood socioeconomic disadvantage was not associated with organizational resource access. Implications for assessment and community development efforts are discussed.